The role of mesenchymal stem cells derived exosomes as a novel nanobiotechnology target in the diagnosis and treatment of cancer - Zhou, You; Dong, Yuqing; Zhang, Aixue; Wu, Jibin; Sun, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stem cells (MSCs), one of the most common types of stem cells, are involved in the modulation of the tumor microenvironment (TME). With the advancement of nanotechnology, exosomes, especially exosomes secreted by MSCs, have been found to play an important role in the initiation and development of tumors. In recent years, nanobiotechnology and bioengineering technology have been gradually developed to detect and identify exosomes for diagnosis and modify exosomes for tumor treatment. Several novel therapeutic strategies bioengineer exosomes to carry drugs, proteins, and RNAs, and further deliver their encapsulated cargoes to cancer cells through the properties of exosomes. The unique properties of exosomes in cancer treatment include targeting, low immunogenicity, flexibility in modification, and high biological barrier permeability. Nevertheless, the current comprehensive understanding of the roles of MSCs and their secreted exosomes in cancer development remain inadequate. It is necessary to better understand/update the mechanism of action of MSCs-secreted exosomes in cancer development, providing insights for better modification of exosomes through bioengineering technology and nanobiotechnology. Therefore, this review focuses on the role of MSCs-secreted exosomes and bioengineered exosomes in the development, progression, diagnosis, and treatment of cancer.